Cytotoxic triterpenoid glycosides (saikosaponins) from the roots of Bupleurum chinense. Issue 18 (15th September 2015) - Li, Dan-Qi; Wu, Jie; Liu, Li-Yin; Wu, Ying-Ying; Li, Ling-Zhi; Huang, Xiao-Xiao; Liu, Qing-Bo; Yang, Jing-Yu; Song, Shao-Jiang; Wu, Chun-Fu
Graphical abstract